Characteristics Analysis and Detection Algorithm of Mosquitoes - Jahangir Alam S.M.; Hu Guoqing; Cheng Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The systematic detection and elimination of mosquitoes is a valuable process, the results of which could be important in the fight against Malaria. In this study, image processing is used, allowing the researchers to detect the mosquitoes and their locations. Mosquitoes' physical characteristics, territorial and behavioral patterns were also analyzed through recognition technology. It is found that mosquitoes can be detected and differentiated by their physical, territorial and behavioral patterns through these methodologies. In addition to mosquitoes, flies and bees are also included in this study and were analyzed for their patterns, as well as their distinguishing features. Size, number of objects, proboscis, body shape, color, antennae, hind legs, and shape parameters were all factors considered for mosquito detection with image processing. All these informations were used in the Mosquito Detection Algorithm. This study provides characteristic descriptions of all three insects and statistical analysis of the data found.